Fiduciary Criminal Liability for the Transfer of Fiduciary Guarantee Objects without the Fiduciary Owner's Consent - Risno Adam; Darmawati Darmawati; Apriyanto Nusa Ariyanto (Indonesian Journal of Innovation Multidisipliner Research, 2026)
This study aims to analyze the criminal law enforcement against the transfer of fiduciary collateral objects by the fiduciary grantor at the Pohuwato Resort Police, as well as the factors influencing it. This issue is important because, in financing practices, fiduciary collateral objects often remain under the control of the debtor, creating the potential for such objects to be transferred, pledged, or leased without the written consent of the fiduciary recipient. This study employs a normative-empirical legal research method with a qualitative approach. Data were obtained through literature studies, interviews, observation, and documentation involving police officers, financing companies, and relevant case documents. The results show that criminal law enforcement against the transfer of fiduciary collateral objects has not been optimally implemented. Although Article 23 paragraph (2) and Article 36 of Law Number 42 of 1999 concerning Fiduciary Security regulate prohibitions and criminal sanctions, their implementation still faces obstacles at the investigation and inquiry stages. These obstacles include difficulties in proving the offense, limited documentation, difficulties in tracing collateral objects, and differing understandings between civil default and fiduciary crimes. This condition weakens legal protection for creditors and reduces legal certainty in financing relationships. This study emphasizes the need to improve the professionalism of investigators, strengthen coordination with financing companies, and enhance the administration of fiduciary security in order to realize legal certainty and legal protection for creditors. The findings are expected to serve as input for law enforcement officials in handling fiduciary cases effectively.